The Effect of Migration Experience on Occupational Mobility in Estonia - Jaan Masso; Raul Eamets; Pille M\~otsmees (Institute for the Study of Labor (IZA), 2013)
The existing literature on return migration has resulted in several studies analysing the impact of foreign work experience on the returnees' earnings or their decision to become self-employed; however, in this paper we analyse the less studied effect on occupational mobility - how the job in the home country after returning compares to the job held before migration. The effect of temporary migration on occupational mobility is analysed using unique data from an Estonian online job search portal covering approximately 10-15% of the total workforce, including thousands of employees with temporary migration experience. The focus on data from a Central and Eastern European country is motivated given that the opening of labour markets in old EU countries to the workforce of the new member states has led to massive East-West migration. We did not find any positive effect of temporary migration on upward occupational mobility and in some groups, such as females, the effect was negative. These results could be related to the typically short-term nature of migration and occupational downshifting abroad as well as the functioning of the home country labour market.
Keywords: F22; J62; 330; occupational mobility; temporary migration; Central- and Eastern Europe